2015
DOI: 10.1097/iae.0000000000000527
|View full text |Cite
|
Sign up to set email alerts
|

Directional Optical Coherence Tomography Provides Accurate Outer Nuclear Layer and Henle Fiber Layer Measurements

Abstract: Purpose The outer nuclear layer (ONL) contains photoreceptor nuclei, and its thickness is an important biomarker for retinal degenerations. Accurate ONL thickness measurements are obscured in standard optical coherence tomography (OCT) images because of Henle fiber layer (HFL). Improved differentiation of the ONL and HFL boundary is made possible by using Directional OCT (D-OCT), a method that purposefully varies the pupil entrance position of the OCT beam. Methods Fifty-seven normal eyes were imaged using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
111
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 34 publications
5
111
0
2
Order By: Relevance
“…Accordingly, it has been shown that extracting the asymmetric component of photoreceptor reflectance (split-detection 27 ) is a powerful means for the identification of cones in a dystrophic retina. The Henle fibers, [28][29][30] the nerve fiber layer, 31 and Gunn's dots 32 also show strong directional reflectance; hence, multiangle imaging appears as a necessary procedure for adequate interpretation of high-resolution retinal imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it has been shown that extracting the asymmetric component of photoreceptor reflectance (split-detection 27 ) is a powerful means for the identification of cones in a dystrophic retina. The Henle fibers, [28][29][30] the nerve fiber layer, 31 and Gunn's dots 32 also show strong directional reflectance; hence, multiangle imaging appears as a necessary procedure for adequate interpretation of high-resolution retinal imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In the earlier study, widening of the ONL was considered as the last factor determining foveal immaturity [6], and in the current study, we considered that analysis of the outer retinal layers (OPL+HFL+ONL) could allow a more precise evaluation of eyes with foveal hypoplasia exhibiting severe structural immaturity. In OCT images, the classical ONL, which extends from the end of the OPL to the external limiting membrane, can be divided into the HFL and true ONL, and this distinction results in a more precise structural analysis of the outer retina [9][10][11]. Focusing on the HFL appearance, the OCT findings can be classified into three types even in eyes with foveal hypoplasia exhibiting severe structural abnormalities (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In retinal imaging systems, knowledge of the pupil entry position and scan location at the retinal plane can result in enhanced knowledge of the beam trajectory through the subject's eye that can elucidate the illumination incidence angle at the retinal plane. As discussed above, there are a variety of retinal structures that exhibit illumination directionality dependence [6][7][8][9][10][11][12][13][14][15][16]. Previous studies exploring this dependence varied the pupil entry position manually and therefore were subject to motion artifacts that hindered repeatability.…”
Section: Discussionmentioning
confidence: 99%
“…By displacing the OCT beam laterally, the collected back-scattered intensity of HFL increased on the opposite side of the foveal pit from the pupil entry offset, resulting in enhanced OCT visibility due to nearly normal illumination relative to HFL fibers in that region. Using eccentric pupil entry positions in a technique called Directional OCT, visualization of HFL enabled anatomically correct ONL thickness measurements [15,16]. However, similar to previous studies, the pupil entry position manual displacement was subject to patient motion and operator misalignment.…”
Section: Introductionmentioning
confidence: 91%